Vochysia microphylla (Vochysiaceae), a new species from Serra do Cipó, Minas Gerais, Brazil - Shimizu, Gustavo Hiroaki; Rodrigues, Licléia Da Cruz; Yamamoto, Kikyo (Phytotaxa, 2012)
Vochysia microphylla is described and illustrated as a new species. It belongs to Vochysia section Ciliantha subsection Lutescentes. This new species is apparently endemic to the “campos rupestres” vegetation in Morro do Pilar and Itambé do Mato Dentro, Serra do Cipó, Minas Gerais, Brazil.